سرالإيجاز والإطناب دراسة تحليلية بلاغية - Antoro, Asmakin (Program Studi Pendidikan Bahasa Arab, 2024)
This analytical rhetorical study explores the concept of brevity (Ijaz) and elaboration (Itnaab) within Arabic literature and the Qur'an. Ijaz, or brevity, is defined as the expression of a substantial meaning through few words, which, despite their conciseness, fully convey the intended message. In contrast, Itnaab, or elaboration, refers to the art of extending and expanding on a meaning through additional words, providing deeper clarification or emphasis. Both linguistic phenomena serve distinct rhetorical purposes in enhancing the communication of ideas, whether through subtlety or emphasis. The study delves into examples from classical Arabic literature and the Qur'anic text, illustrating how each technique plays a vital role in effective expression. Through a detailed analysis of various passages, this study highlights the balance between conciseness and elaboration in Arabic rhetoric and their respective roles in conveying complex ideas, emotions, and theological concepts. The findings emphasize that both Ijaz and Itnaab contribute to the richness and depth of Arabic and Qur'anic discourse.